Eco-design and eco-efficiency competencies development in engineering and design students - Neto, Victor (2019)
The development of vital competencies and a mindset to rethink products, production, and business models in engineering and design students is presently of great importance. These future professionals will play a key role in the development of sustainable products. Within Eco-design and Eco-efficiency curricular unit, an assignment was developed that consisted of the development of an eco-design and eco-efficiency study of a given product, provided by a real industrial company. In this paper, the challenge description and application are reported, as well as the key conclusions.